1990
DOI: 10.1111/j.1469-7610.1990.tb01576.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivity and Parental Psychopathology

Abstract: The association of child hyperactivity and parental psychopathology was explored by establishing lifetime DSM-III diagnoses and histories of childhood hyperactivity among the parents of boys, aged 7-11 yrs, in five diagnostic groups: attention deficit disorder with hyperactivity (ADDH), conduct disorder (CD), ADDH + CD, emotional disorder (ED) and no disorder (NC). These groups were differentiated by a family history of parental psychopathology or childhood hyperactivity. ADDH + CD, CD and ED groups all had si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
3

Year Published

1990
1990
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 24 publications
1
43
3
Order By: Relevance
“…Previous evidence suggested that ODD is a mild variant of CD [41,42,50]. Findings of the present study are in accordance with above-mentioned evidence.…”
Section: Discussionsupporting
confidence: 83%
“…Previous evidence suggested that ODD is a mild variant of CD [41,42,50]. Findings of the present study are in accordance with above-mentioned evidence.…”
Section: Discussionsupporting
confidence: 83%
“…Compared with controls, mothers with CI from our study report more cognitive and affective symptoms, consistent with the broader literature showing increased cognitive and mood disorders among families with children with ASD and ADHD. 46,47 Notably, compared with mothers of controls, mothers of children with ASD or ADHD were significantly more likely to report that their chil- Items are scaled from 1 to 10, then summed across items for the total score, with a total possible range from 0 to 100. The range for mothers of control children was 0 to 83, 1 to 93 for mothers of children with attention deficit hyperactivity disorder (ADHD), and 0 to 95 for mothers of children with autism spectrum disorder (ASD).…”
Section: Discussionmentioning
confidence: 99%
“…Another plausible explanation for moderator effect of ADHD status for pervasiveness was that a high proportion of fathers of children with ADHD have high levels of ADHD symptoms themselves (Schachar, & Wachsmuth, 1990) our sample was typical in this regard in that two thirds of the fathers were diagnosed or suspected they had ADHD. Because fathers are likely to share some of the ADHD behavioural characteristics with their youth, such as being inattentive, disorganized, and having low tolerance for frustration, they may be less tolerant of their sons' or daughters' misbehaviour (Psychogiou, Daley, Thompson, & Sonuga-BArke, 2007).…”
Section: Father-reported Attributions For Conflict With Adolescentsmentioning
confidence: 99%